PENGARUH LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN KEWIRAUSAHAAN DI KELAS XI PERHOTELAN SMK NEGERI 4 KOTA JAMBI - Rahayu, Yulia Dina; Indra Yudha, Redi (Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of the school environment on student learning outcomes in the subject of entrepreneurship in class XI Hospitality SMK N 4 Jambi City. The research that the researchers did was a survey method. The population of this study amounted to 60 students. The sample technique in this study was proportional random sampling so that 52 students were selected as the research sample. The data collection technique in this study was by distributing questionnaires to research respondents. The data analysis technique in this study was simple regression analysis using the SPSS for Windows Version 22 program. Based on the results of the study, it was concluded that the school environment variables were in the sufficient category. This is shown by the average school environment variable which is 3.60 with the Respondent's Achievement Level (TCR) of 72.09. It is shown that the school environment variable (X) is not significant to student learning outcomes (Y), because the value of Sig tcount is 1.216 while ttable is 2.007 meaning that tcount < ttable is 1.216 < 2.007. Keywords: School Environment, Learning Outcomes